High-resolution app data reveal sustained increases in recreational fishing effort in Europe during and after COVID-19 lockdowns - Audzijonyte, Asta; Mateos-González, Fernando; Dainys, Justas; Gundelund, Casper; Skov, Christian; Tyrell DeWeber, J; Venturelli, Paul; Vienožinskis, Vincentas; Smith, Carl (Royal Society open science, 2023)
It is well recognized that COVID-19 lockdowns impacted human interactions with natural ecosystems. One example is recreational fishing, which, in developed countries, involves approximately 10% of people. Fishing licence sales and observations at angling locations suggest that recreational fishing effort increased substantially during lockdowns. However, the extent and duration of this increase remain largely unknown. We used four years (2018-2021) of high-resolution data from a personal fish-finder device to explore the impact of COVID-19 lockdowns on angling effort in four European countries. We show that relative device use and angling effort increased 1.2-3.8-fold during March-May 2020 and generally remained elevated even at the end of 2021. Fishing during the first lockdown also became more frequent on weekdays. Statistical models explained 50-70% of the variation, suggesting that device use and angling effort were relatively consistent and predictable through space and time. Our study demonstrates that recreational fishing behaviour can change substantially and rapidly in response to societal shifts, with profound ecological, human well-being and economic implications. We also show the potential of angler devices and smartphone applications for high-resolution fishing effort analysis and encourage more extensive science and industry collaborations to take advantage of this information.
Keywords: smartphone applications; non-probabilistic methods; inland and coastal fisheries; anthropause; COVID-19; recreational fishing effort